Clinical-based Cell Therapies for Heart Disease—Current and Future State - Turner, Darren (Rambam Maimonides Med J, 2020)
Patients have an ongoing unmet need for effective therapies that reverse the cellular and functional damage associated with heart damage and disease. The discovery that ~1%–2% of adult cardiomyocytes turn over per year provided the impetus for treatments that stimulate endogenous repair mechanisms that augment this rate. Preclinical and clinical studies provide evidence that cell-based therapy meets these therapeutic criteria. Recent and ongoing studies are focused on determining which cell type(s) works best for specific patient population(s) and the mechanism(s) by which these cells promote repair. Here we review clinical and preclinical stem cell studies and anticipate future directions of regenerative medicine for heart disease.